2012
DOI: 10.1007/s10563-012-9137-0
|View full text |Cite
|
Sign up to set email alerts
|

Partial Oxidation of Methane to Nitrogen Free Synthesis Gas Using Air as Oxidant

Abstract: In order to generate synthesis gas or hydrogen free from nitrogen by partial oxidation of methane using air as an oxidant, gas-solid reactions of methane and a metal oxide and/ or mixed metal oxides were carried out. The background of the gas-solid reaction was briefly reviewed and then a series of the present author's studies was described. As metal oxides Fe 2 O 3 and NiO were active, but the reaction with methane and these oxides afforded complete oxidation to give H 2 O and CO 2 . To both oxides, addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Through this process, not only syngas was obtained, the environmental friendly energy carrier hydrogen also can be produced via two steps, without requiring additional gas treatments such as reforming or shifting and separation processes. In previous researches, various metals [12,13] , complex metals [14,15] , perovskite oxides [16][17][18] or double perovskite-type oxides [5] had been used as catalysts for methane conversion. Results showed that perovskite-type oxides exhibited excellent performance with high catalytic activity and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Through this process, not only syngas was obtained, the environmental friendly energy carrier hydrogen also can be produced via two steps, without requiring additional gas treatments such as reforming or shifting and separation processes. In previous researches, various metals [12,13] , complex metals [14,15] , perovskite oxides [16][17][18] or double perovskite-type oxides [5] had been used as catalysts for methane conversion. Results showed that perovskite-type oxides exhibited excellent performance with high catalytic activity and stability.…”
Section: Introductionmentioning
confidence: 99%
“…Fe 2 O 3 as oxygen carrier was proved to own the ability for methane combustion [7,8], but addition of other suitable oxides can modify the selectivity of its lattice oxygen for selective oxidation of methane to syngas. Fe 2 O 3 -Rh 2 O 3 /Y 2 O 3 and Fe 2 O 3 -Cr 2 O 3 -MgO oxides were found to be active to produce syngas with a moderate methane conversion and selectivity [64]. It is also proved that combining CuO and Fe 2 O 3 to form a Cu-ferrite could obtain a suitable oxygen carrier for methane selective oxidation.…”
Section: Other Oxygen Carriersmentioning
confidence: 92%
“…During the reaction between methane and NiO-based oxides, the syngas yield depends on the oxidation degree of the oxygen carriers: highly oxidized oxide particles resulted in the formation of CO 2 and H 2 O, while reduced particles could produce CO and H 2 [70,74]. Addition of Cr 2 O 3 into NiO-MgO system could change reactivity of the lattice oxygen in the materials, and the fully oxidized NiO-Cr 2 O 3 -MgO produced H 2 and CO with high selectivity during the reaction with CH 4 [64,75]. The appearance of NiAl 2 O 4 also could reduce the activity of oxygen in the material and promote the formation of H 2 and CO [76].…”
Section: Other Oxygen Carriersmentioning
confidence: 99%
“…Fe-based oxides are active in the water splitting reaction; however, they have high selectivity for total methane oxidation, making them less useful for syngas production. Some complex metal oxides, like CuO-Fe 2 O 3 , Fe 2 O 3 -Rh 2 O 3 /T 2 O 3 , Fe 2 O 3 -Cr 2 O 3 -MgO, are helpful for syngas production, but the methane conversion is moderate. , …”
Section: Hydrogen Generation Processesmentioning
confidence: 99%
“…Some complex metal oxides, like CuO-Fe 2 O 3 , Fe 2 O 3 -Rh 2 O 3 /T 2 O 3 , Fe 2 O 3 -Cr 2 O 3 -MgO, are helpful for syngas production, but the methane conversion is moderate. 19,20 Dry CO 2 reforming of methane (DRM) is another process for hydrogen production that is worth discussing. DRM requires high temperatures from 800 to 1000 °C due to the highly endothermic characteristics of reaction.…”
Section: Hydrogen Generation Processesmentioning
confidence: 99%